Nusinersen for spinal muscular atrophy type 1: Real‐world respiratory experience. Issue 1 (5th November 2020) - Lavie, Moran; Diamant, Nir; Cahal, Michal; Sadot, Efraim; Be'er, Moria; Fattal‐Valevski, Aviva; Sagi, Liora; Domany, Keren A.; Amirav, Israel
Abstract: Background: The emergence of new treatments for spinal muscular atrophy (SMA) is revolutionary, especially for SMA type 1 (SMA1). Data on respiratory outcomes remain sparse and rely mostly on randomized clinical trials. We report our experience of Nusinersen‐treated SMA1 patients in real‐world settings. Methods: Data from SMA1 patients treated with Nusinersen were prospectively collected between 1/2017 and 1/2020. Respiratory variables included the use of assisted ventilation, the use of mechanical insufflation‐exsufflation (MIE), respiratory complications, and death or treatment cessation due to respiratory reasons. Results: Twenty SMA1 patients were assessed before and after 2 years of Nusinersen treatment which was initiated at a median age of 13.5 months (range, 1–184). At baseline, 16 patients were using assisted ventilation, eight noninvasive and eight invasive. Twelve patients were using permanent ventilation and four partial ventilation. After 2 years of treatment, there was no change in respiratory support among ventilated patients. All four patients who were free from respiratory support at baseline required the initiation of assisted ventilation during the study period. All 20 patients used MIE after 2 years of treatment. Two patients died from acute respiratory failure and one sustained severe brain injury. Four patients had chronic and/or recurrent atelectasis. Conclusion: Most of our patients were stable in their need for assisted ventilation and did not worsen as expected in SMA1, nor did they improve as might be hoped. Future studies are needed to determine if earlier treatment with Nusinersen might result in respiratory outcomes superior to those reported in this real‐life study.